Erratum for Mirhendi et al.,the first case of onychomycosis in a koala (phascolarctos cinereus) due to atypical isolates of Microsporum gypseum, a diagnostic challenge - hossein mirhendi; Yayoi Nishiyama; Ali Rezaei-Matehkolaei; Kazuo Satoh; Koichi Makimura (Mazandaran University of Medical Sciences, 2018)
Erratum for Mirhendi et al., the first case of onychomycosis in a koala (phascolarctos cinereus) due to atypical isolates of Microsporum gypseum, a diagnostic challenge Mirhendi H1,2*, Nishiyama Y3, Rezaei-Matehkolaei A4, Satoh K5, Makimura K5 1. Department of Medical Parasitology & Mycology, School of Medicine, Isfahan University of Medical Sciences, Isfahan, Iran 2. Department of Medical Parasitology & Mycology, School of Public Health, Tehran University of Medical Sciences, Tehran, Iran 3. Teikyo University Institute of Medical Mycology, Tokyo, Japan 4. Department of Medical Mycology, School of Medicine, Health Research Institute, Infectious and Tropical Diseases Research Center, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran 5. General Medical Education and Research Center, Teikyo University, Tokyo, Japan   ERRATUM Volume 2, no. 2, 45-50, 2016, DOI:10.18869/acadpub.cmm.2.2.2.  The original version of this article contained incorrect dose of terbinafine. This erratum adds the correct dose as shown below. Terbinafine dosage should change from 250 mg/kg to 250 mg/day.